Arthropoda diversity in irrigated rice under different organic fertilization regimes - Menegon, Leandro Luiz (2021)
Rice fields are agroecosystems that can hold a rich diversity of plants and animals, depending on the management to which they are submitted. This study aimed to evaluate arthropods associated with irrigated rice with organic management during the period of vegetative and reproductive development of the crop comparing the diversity in response to two organic compounds in different doses. The treatments were: Control (without application of compost); 2, 4 e 6 t ha-1 of two organic compost (Ecocitrus® and Folhito®). In each treatment were defined three transects which form covered with sweep net to collect the arthropods, twice a month from December 2013 to February 2014. Were collected 41.236 arthropods of 11 orders. The most abundant orders were Diptera, Hemiptera, Odonata, Orthoptera, Coleoptera and Araneae. Hymenoptera, Lepidoptera, Blattodea, Neouroptera and Phasmatodea were less abundant. This is the first record of Schizaphis graminum in irrigated rice in Brazil. There was no difference in the collection number by transect among the treatments during the rice cycle. The greatest abundance of arthropods was recorded at the beginning of the reproductive stage of the culture.